AI 2008 : advances in artificial intelligence : 21st Australasian Joint Conference on Artificial Intelligence, Auckland, New Zealand, December 1-5, 2008, proceedings - Wobcke, Wayne (Springer, 2017)
This book constitutes the refereed proceedings of the 21th Australasian Joint Conference on Artificial Intelligence, AI 2008, held in Auckland, New Zealand, in December 2008.